Solutions for the stabilization of lagoonal inlets in the coastal zone of Central Vietnam - Thanh, Tran Duc; Vinh, Vu Duy; Nhon, Dang Hoai; Vuong, Bui Van (Vietnam Journal of Marine Science and Technology, 2019)
Of the 14 inlets belonging to 12 coastal lagoons in the coastal zone of Central Vietnam, the unstable group consists of 4 inlets; the less stable group comprises 4 inlets and the relatively stable group has 6 inlets. For the feasibility and effectiveness, the constructions of stabilizing lagoonal inlets must be multi-purpose and multi-benefit, such as maintenance of ecosystems, opening to the sea for ships and boats, flood drainage and pollution limitation. They need to be combined with other development activities to reduce costs and increase benefits, for example in conjunction with seaports, fishing harbours, typhoon shelters and tourism... Solutions to stabilise the lagoonal inlets consist of 5 groups: Constructing groins for control of inlets; dredging lagoonal inlets and bottom; preventing coastal erosion outside the lagoons; stabilizing the lagoon banks and the surrounding sandy areas; regulating water supplies in the catchments into the lagoons. Depending on the natural conditions and degrees of human impact, the priority solution has been proposed for each lagoonal inlet.